Kepemimpinan transformasional dan transaksional terhadap perilaku inovatif: Mediasi oleh Variabel Psychological Empowerment - Agi Syarif Hidayat; Hilmiana Hilmiana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
and transactional leadership on innovative behavior with psychological empowerment as the moderator variable. The research method used is quantitative research methods. The population in this study were employees of the Regional Drinking Water Company (PDAM) of Cirebon City with a total population of 203 people. The sampling measurement technique used the Slovin formula with a margin of error of 10%, so the number of samples in this study was determined to be 67 respondents. The sampling technique uses the incidental sampling approach. The data collection technique used was a questionnaire with a Likert scale. The data analysis technique used is path analysis. The results showed that transformational leadership had a significant effect on innovative behavior either directly or mediated by psychological empowerment variables. The transactional leadership variable did not have a significant effect on innovative behavior either directly or mediated by psychological empowerment variables. The psychological empowerment variable has a significant effect on increasing innovative behavior.